1999
DOI: 10.1177/00220345990780080801
|View full text |Cite
|
Sign up to set email alerts
|

Mandibulofacial Adaptations in a Juvenile Animal Model of Temporomandibular Joint Arthritis

Abstract: Juvenile rheumatoid arthritis (JRA) is a chronic systemic disease of childhood that affects synovial joints including the temporomandibular joint (TMJ). Individuals with JRA of the TMJ frequently show aberrations in mandibulofacial development. Since the basis for these developmental perturbations is poorly understood, they remain a perplexing clinical problem to manage. To begin dissecting the mechanisms for altered craniofacial development in JRA of the TMJ, we characterized the gross morphologic adaptations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Our sample represents adults between 20 to 60 years of age with non-severe rheumatoid arthritis or non-severe temporomandibular symptoms related to severe rheumatoid arthritis. We consider that the increase in RMS activity in patients with rheumatoid arthritis could be observed in patients with non-severe symptoms or as an onset of muscular disturbance, and muscular hyperactivity could be a first sign before a chronic muscular disturbance takes place [7,2,25,9]. Our results show a decreased rate of muscular activity with age and a decreased rate during the evaluated period in rheumatic patients.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Our sample represents adults between 20 to 60 years of age with non-severe rheumatoid arthritis or non-severe temporomandibular symptoms related to severe rheumatoid arthritis. We consider that the increase in RMS activity in patients with rheumatoid arthritis could be observed in patients with non-severe symptoms or as an onset of muscular disturbance, and muscular hyperactivity could be a first sign before a chronic muscular disturbance takes place [7,2,25,9]. Our results show a decreased rate of muscular activity with age and a decreased rate during the evaluated period in rheumatic patients.…”
Section: Discussionmentioning
confidence: 50%
“…We have non-cephalometric information of these patients and we were unable to evaluate the association of posterior mandibular height, condylar neck height, and total mandibular length that have been associated with the RMS mean described as mandibulofacial or masticatory muscular adaptations [27,25]. However, few studies [4,17,7] have used electromyographic evaluation and more research on this topic is needed in order to clarify or identify electromyographic activity patterns that could suggest the onset of muscular activity disturbance and at the same time present different patterns according to the severity of rheumatoid arthritis.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…34 In a later cephalometric study, diminished dimensions of the mandible were found in arthritic animals. 35 These findings were confirmed by Stoustrup et al studying growing rabbits with induced TMJ arthritis using medical computed tomography (CT). 36 The images of the CT scans were superimposed, and the difference between normal and abnormal growth caused by TMJ arthritis was visualized (Fig.…”
Section: Mandibular Growth Deviationmentioning
confidence: 74%
“…and Tominaga et al. to examine the antigen‐induced arthritis in the rabbit's temporomandibular joint .…”
Section: Discussionmentioning
confidence: 99%